Bottom trawling reduces benthic denitrification and has the potential to influence the global nitrogen cycle. Issue 3 (14th February 2020) - Ferguson, Angus J. P.; Oakes, Joanne; Eyre, Bradley D.
Abstract: Bottom trawling and eutrophication are large stressors that are critically coupled. Here we show, using a before‐after control‐effect design, the significant reduction in denitrification as a result of experimental bottom trawling in a shallow coastal system. Trawl disturbance destroys the complex three‐dimensional redox structures in surface sediments that maximize denitrification potential, resulting in up to a 50% reduction in net denitrification. The decrease in net denitrification also increased after each trawling event suggesting a declining resilience to trawling and eutrophication. Bottom trawling occurs at such a large scale that it could result in significant amounts of nitrogen being retained on the continental shelf. As such, impacts on the global ocean nitrogen cycle and associated eutrophication should be counted among the many negative consequences of extensive seafloor trawling.